2021
DOI: 10.3389/fcvm.2020.629933
|View full text |Cite
|
Sign up to set email alerts
|

Why Is COVID-19 More Severe in Patients With Diabetes? The Role of Angiotensin-Converting Enzyme 2, Endothelial Dysfunction and the Immunoinflammatory System

Abstract: Meta-analyses have indicated that individuals with type 1 or type 2 diabetes are at increased risk of suffering a severe form of COVID-19 and have a higher mortality rate than the non-diabetic population. Patients with diabetes have chronic, low-level systemic inflammation, which results in global cellular dysfunction underlying the wide variety of symptoms associated with the disease, including an increased risk of respiratory infection. While the increased severity of COVID-19 amongst patients with diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 323 publications
(337 reference statements)
4
51
0
Order By: Relevance
“…With endothelial conditions that are already compromised by this process, it cannot be denied that endothelial dysfunction will worsen with COVID-19, particularly in older patients. 13 thrombin-antithrombin-complex and D-dimer after administration of 4 Â 10 6 cells/kg body weight AT-MSCs; thus, an application dose less than 4 Â 10 6 cells/kg body weight is recommended. 16 Not analyzing the TF/CD142, we used UC-MSCs with 1 Â 10 6 /kg body weight dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With endothelial conditions that are already compromised by this process, it cannot be denied that endothelial dysfunction will worsen with COVID-19, particularly in older patients. 13 thrombin-antithrombin-complex and D-dimer after administration of 4 Â 10 6 cells/kg body weight AT-MSCs; thus, an application dose less than 4 Â 10 6 cells/kg body weight is recommended. 16 Not analyzing the TF/CD142, we used UC-MSCs with 1 Â 10 6 /kg body weight dose.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction occurs in patients with diabetes because of oxidative stress processes and chronic inflammation. With endothelial conditions that are already compromised by this process, it cannot be denied that endothelial dysfunction will worsen with COVID‐19, particularly in older patients 13 …”
Section: Discussionmentioning
confidence: 99%
“…As reported in the literature, an interaction between COVID-19 and glucose-insulin metabolic disorders is postulated in adults [1,29] and not excluded in pediatrics [30,31]. In particular, the relationship between COVID-19 and type 2 diabetes mellitus (T2DM) has been extensively described in adults [1,2,30] and a relationship between SARS-CoV-2 infection and type 1 diabetes mellitus (T1DM) has also been discussed in children [30][31][32][33][34][35][36]. This is possibly the first up-to-date study on the relationship between IR and glycemic fluctuation in normal weight children without glycemic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that patients with type 2 diabetes (T2D) have an increased risk of morbidity and mortality in the setting of COVID-19 infection [ 5 , 6 , 7 ]. This is thought to be primarily mediated by the alteration of the immune system and renin-angiotensin-aldosterone systems, endothelial dysfunction, and oxidative stress due to chronic hyperglycemia [ 8 , 9 ]. In addition, recent evidence has highlighted not only that the severe systemic inflammation seen in COVID-19 patients causes stress-induced hyperglycemia, but also that SARS-CoV-2 can directly infect the pancreatic β-cells, resulting in β-cell dysfunction and insulin deficiency [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%